Gender-specific capacity of insulin resistance proxies to predict functional decline in older adults - Mariam El Assar; Javier Angulo; José Antonio Carnicero; Begoña Molina-Baena; Francisco José García-García; Patricia Sosa; Leocadio Rodríguez-Mañas (Elsevier, 2024)
Objectives: Insulin resistance determined by Homeostasis Model of Insulin Resistance (HOMA-IR) has been associated with functional decline in non-diabetic older subjects. However, insulin is not routinely assessed. The study evaluated the predictive value of non-insulin-dependent IR surrogates on functional decline in non-diabetic older men and women. Design and participants: Prospective cohort study over 5 years. The study included 615 older participants from the Toledo Study of Healthy Aging. Methods: Frailty was assessed by the Frailty Trait Scale-5 (FTS-5) at baseline and after 5 years follow-up. 193 subjects experienced functional decline (2.5-point reduction in the FTS-5 score). Multivariate regression models analysed the effect of five described IR surrogates on functional decline considering potential confounders. Results: Among evaluated IR proxies, triglyceride glucose-body mass index (TyG-BMI) and HOMA-IR were significantly associated with an increased risk of functional decline (odd ratio (95% confidence interval) TyG-BMI: 1.16 (1.05, 1.28), p = 0.0035 and HOMA-IR: 1.59 (1.15, 2.21), p = 0.0056) among all participants. When stratified by gender, HOMA-IR was related to functional decline in men [2.02 (1.13, 3.59), p = 0.0173] and TyG-BMI in women [1.19 (1.05, 1.35), p = 0.0057]. Conclusions: Only TyG-BMI index mimics the predictive capacity of insulin-based IR marker. The predictive ability of IR indexes is gender-specific, being TyG-BMI the only index able to predict functional decline in women and HOMA-IR in men.